Focusing on malignant tumors: September issue @ a glance - Diaconu Camelia (Archives of the Balkan Medical Union, 2018)
The September issue of the journal “Archives of the Balkan Medical Union“ is ready and has lots of interesting subjects for its readers. Diffuse large B‑cell lymphoma is a common form of non‑Hodgkin’s malignant lymphomas, occurring at all ages.